An interpretive study of the role of teacher beliefs in the implementation of constructivist theory in a secondary school mathematics classroom - Taylor, Peter C. (Curtin University, 1992)
This thesis addresses the internationally recognised problem of transforming classroom teaching that is underpinned by transmissionist epistemologies, especially in the field of mathematics education. A constructivist-related theory of pedagogical reform was derived from the research literature in the fields of teacher cognition and conceptual change theory for the purpose of facilitating the radical reconstruction of teachers' centralist classroom roles and the development of pedagogies aimed at enhancing students' conceptual development. The thesis reports a collaborative action research study which was conducted with a teacher of high school mathematics who attempted to develop a constructivist- oriented teaching approach in his Grade 12 mathematics class.An interpretive research approach (Erickson, 1986) was employed to generate an understanding of the complex network of teacher beliefs and their constraining influence on the radical reform of the teacher's centralist pedagogy. An emergent research focus was the efficacy of the theory of pedagogical reform, especially its underpinning constructivist theory which shaped my discourse with the teacher during the collaborative phase of the study. Data were obtained from classroom participant- observations, teacher and student interviews, the teacher's report on the study, and an application of the repertory grid technique that was designed to investigate the teacher's implicit pedagogical beliefs.The major pedagogical reforms that resulted from the collaborative phase of the study included (1) the teacher's adoption of the role of teacher as learner; and (2) the refinement, rather than radical reform, of his centralist classroom role of teacher as informer. Although the reforms provided enriched opportunities for the development of students' algorithmic abilities, they largely failed to enhance students' mathematical conceptual development.Interpretive analyses were conducted from multiple constructivist-related perspectives (radical constructivism, social constructivism, critical constructivism) in order to generate a better understanding of the narrow scope of the pedagogical reforms. These analyses revealed (1) that rationalist preconceptions of mathematics and mathematical cognition underpinned important aspects of both the theory of pedagogical reform and the teacher's refined centralist classroom role of teacher as interactive informer, and (2) that the teacher's technical rationality, which was buttressed by personally constraining beliefs, maintained the ascendency of his technical curriculum interests and sustained his centalist classroom role of teacher as controller.The results of this thesis suggest strongly, therefore: (1) that pedagogical reforms which are based largely on a cognitivist theory of constructivism are susceptible to being subsumed by a powerful technical-rationalist ideology, and (2) that the hegemonic nature of this ideology is capable of disempowering reform-minded teachers from realising the practical viability of their constructivist-related ideals.The thesis recommends that future constructivist-related pedagogical reform in high school mathematics be based on a critical constructivist perspective which focuses attention on the curriculum interests that govern teaching and learning activities. In particular, it is recommended that reform-minded teachers establish a Critical classroom discourse which aims to attain a balanced rationality by making visible and subject to critical examination the hidden frames of reference that constitute the prevailing rationality of the traditional mathematics classroom.